The earnings effect of education at community colleges - Dave E. Marcotte (Institute for the Study of Labor (IZA), 2006)
In this paper, I make use of data from the 2000 follow-up of the National Education Longitudinal Survey (NELS) post-secondary education transcript files to extend what is known about the value of education at community colleges. I examine the effects of enrollment in community colleges on students' subsequent earnings. I estimate the effects of credits earned separate from credentials because community colleges are often used as a means for students to engage in study not necessarily leading to a degree or certificate. I find consistent evidence of wage and salary effects of both credits and degrees, especially for women. There is no substantial evidence that enrollment in vocational rather than academic coursework has a particularly beneficial effect, however.
urn:nbn:de:101:1-20090825268
Keywords: 330